Caveolin-1(-/-)- and caveolin-2(-/-)-deficient mice both display numerous skeletal muscle abnormalities, with tubular aggregate formation - Schubert, William; Sotgia, Federica; Cohen, Alex W; Capozza, Franco; Bonuccelli, Gloria; Bruno, Claudio; Minetti, Carlo; Bonilla, Eduardo; Dimauro, Salvatore; Lisanti, Michael P (The American journal of pathology, 2007)
Here, we examine the role of "non-muscle" caveolins (Cav-1 and Cav-2) in skeletal muscle biology. Our results indicate that skeletal muscle fibers from male Cav-1(-/-) and Cav-2(-/-) mice show striking abnormalities, such as tubular aggregates, mitochondrial proliferation/aggregation, and increased numbers of M-cadherin-positive satellite cells. Notably, these skeletal muscle defects were more pronounced with increasing age. Because Cav-2-deficient mice displayed normal expression levels of Cav-1, whereas Cav-1-null mice exhibited an almost complete deficiency in Cav-2, these skeletal muscle abnormalities seem to be due to loss of Cav-2. Thus, Cav-2(-/-) mice represent a novel animal model-and the first genetically well-defined mouse model-that can be used to study the pathogenesis of tubular aggregate formation, which remains a poorly understood age-related skeletal muscle abnormality. Finally, because Cav-1 and Cav-2 were not expressed within mature skeletal myofibers, our results indicate that development of these abnormalities probably originates in stem/precursor cells, such as satellite cells or myoblasts. Consistent with this hypothesis, skeletal muscle isolated from male Cav-3(-/-) mice did not show any of these abnormalities. As such, this is the first study linking stem cells with the genesis of these intriguing muscle defects.